Comparative analysis of the level of satisfaction with the services received at the business incubators in USA and Poland – pre-incubation and incubation stage - Radosław Wolniak (Production Engineering Archives, 2018)
The paper concentrate on the problems of customers satisfaction from services in incubator centres in USA and Poland. The aim of the paper is to analyse the level of satisfaction of Business Incubation Centre on the example of two incubator centres one from USA (Hazelton CAN-Be in Pennsylvania and second in Gliwice Poland). The analysis was conducted in pre-incubation and incubation stage. The analysis was conducted on example of survey analysis in both incubator centres. On the base of achieved results we assessed the priority of customers in each incubator centre.